Production of ethanol from corn: is it still a good investment in Brazil? - Jorge, Catia (Kansas State University, 2021)
The purpose of this thesis is to evaluate on the feasibility for company A to invest in a new ethanol plant in the Center-west of Brazil using corn as the main raw material. Brazil is a large producer of ethanol and it has increased production over the past 5 years. The main contributor to ethanol growth has been government policies regulating greenhouse gases emissions through an increase of biofuels blended into gasoline and diesel. The mandate in Brazil states a blend of a maximum 13% for biofuels in diesel in 2021, of which 80% comes from the soybean feedstocks, and the Government plans to reach B15 by 2023. For ethanol, the mandate for blending in gasoline is 27% and may increase to 30% in 2022 and 40% in 2030. Due to low prices worldwide for sugar, Brazil reduced sugar production by 10% in 2018. Ethanol production has increased by 45% from 2012 to 2019, 24 million m3 to 35 million m3. Ethanol consumption increased to 33 million m3 in 2019. The production of hybrid cars represented 96% of the 2.3 million cars produced during the same year. Government policies and the demand for biofuels has resulted in ethanol representing 42.6% in 2019 of fuel use. More companies are investing in ethanol plants using corn as a feedstock with the majority in the state of Mato Grosso where corn price is lower. The main reasons to locate plants in Mato Grosso are: 1) It is the biggest producer of corn in Brazil, about 30 million mt/year 2) Favorable weather and land for double cropping, which means planting beans and corn in the same crop year - September to August 3) Lower production costs due to double cropping 4) Strategically located in center area, so it can supply northern and northeastern states with lower logistic costs compared to Sao Paulo, the biggest producer of ethanol from sugar cane 5) Land availability to increase eucalyptus production, the main source of energy for the plant boilers 6) Infrastructure investment from the Government of the state of Mato Grosso or any other state to reduce high logistics costs to make Brazilian corn more competitive in the worldwide market 7) Large concentration of cattle for consumption of DDG – Dried Distilled Grains, the main byproduct derived from ethanol production using corn This thesis analyzes if an investment in an ethanol plant in Mato Grosso using corn as the main raw material is profitable.
Keywords: Brazil; Ethanol; Corn; Financial investment; Agribusiness; Agricultural economics